Criminal Action of Cosmetics Without License in Conception of Legal Expression - Lutfi Anindita; Bambang Tri Bawono (Law Development Journal, 2021)
The purpose of this study is to determine and analyze the investigator's authority to handle the distribution of cosmetics without a permit in the construction of the legal system. To find out and analyze the implementation of Article 197 in conjunction with Article 106 paragraph (1) subside Article 196 in conjunction with Article 98 paragraph (2) and paragraph (3) of Act No. 36 of 2009 concerning Health in the conception of legal certainty. The approach method used in the preparation of this legal writing is to use a sociological juridical approach, namely seeing the law as human behavior in society.The specification of this research is descriptive analytical. Based on the results of that research The authorities of investigators to handle the unauthorized distribution of cosmetics in the construction of the legal system include: to receive reports or complaints from someone about the existence of a criminal act; take the first action at the scene; order a suspect to stop and check the suspect's identification; carry out an arrest, detention, search and confiscation; carry out inspection and confiscation of letters; take fingerprints and take a picture of a person; summon people to be heard and examined as suspects or witnesses; bring in the necessary experts in connection with the case examination; to terminate the investigation; take other action according tolaw responsible. Implementation of Article 197 in conjunction with Article 106 paragraph (1) subsidiary to Article 196 in conjunction with Article 98 paragraph (2) and paragraph (3) of Act No. 36 of 2009 concerning Health in the conception of legal certainty it is very appropriate to receive appropriate punishment because actions are very detrimental to the wider community both from an economic, social, and cultural perspective.